High Yielding vs. Low Yielding Testers to Identify Advanced Breeding Lines for General Combining Ability in Dolichos Bean (Lablab purpureus). Issue 1 (2nd January 2016) - Keerthi, C. M.; Ramesh, S.; Byregowda, M.; Rao, A. Mohan; Vaijayanthi, P. V.; Chandrakant, N.; Shivakumar, M. S.
ABSTRACT: Plant breeders are often confronted with the task of selecting suitable parents for making crosses to maximize the probability of isolating desirable pure-lines in predominantly self-fertilizing species, such as dolichos bean. General combining ability (GCA) is one of the widely accepted measures for choosing parents for crosses. However, the choice of suitable testers to discriminate among breeding lines for GCA has been a debatable issue in crop breeding. Comparative ability of high yielding testers (HYT) and low yielding testers (LYT) to discriminate among advanced breeding lines for GCA in dolichos bean was investigated using two criteria: (1) range of GCA and (2) contribution of lines towards total variance of test-cross progenies. The range of estimated GCA effects of lines was wider when tested against LYT than when tested against HYT. The greater contribution of lines to the variance of crosses derived from LYT than those derived from HYT suggested better ability of LYT than HYT to discriminate among lines for GCA. Based on GCA effects, significant differences existed in the ability of HYT and LYT to discriminate among lines for their GCA effects and favored the use of LYT for studies designed to evaluate the breeding lines for their GCA effects in dolichos bean.